STRATEGI FUNDRAISING MELALUI SISTEM PEMBAYARAN DIGITAL QRIS DALAM OPTIMALISASI DANA ZIS DI BAZNAS KABUPATEN BANYUMAS - Ngafifatun Lutfiyan Falihah; Jamal Abdul Aziz (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research analyzes the fundraising strategy for Zakat, Infaq, and Sadaqah (ZIS) implemented by BAZNAS Banyumas Regency through the QRIS digital payment system. Utilizing a descriptive qualitative method, this study involved direct observation of QRIS implementation, in-depth interviews with staff and muzakki (zakat payers), and analysis of ZIS transaction documentation. The findings indicate that the use of QRIS significantly contributed to the increase in ZIS fund collection, evidenced by a rise from IDR 9.49 billion in 2019 to IDR 19.18 billion in 2023. However, QRIS implementation still faces challenges such as low digital literacy among some community members and the lack of separate transaction data for QRIS from bank transfers. This study concludes that more intensive socialization and detailed data management are essential to maximize QRIS's potential, especially in reaching younger generations, and to ensure convenience, transparency, and security for muzakki